Goosebumps Attack of the mutant - Stine, R. L. (Scholastic Inc. New York, 1994)
Skipper Matthews is obsessed with comics, especially the series staring the super villain the Masked Mutant, after an unexpected encounter with the arch-villain, Matt is wondering if he has read one comic too many